2001
DOI: 10.1080/088800101300002946
|View full text |Cite
|
Sign up to set email alerts
|

MUTISM AFTER SURGICAL REMOVAL OF A CEREBELLAR TUMOR: Two Case Reports

Abstract: The authors report two pediatric cases of transient mutism that occurred after surgical removal of a medulloblastoma and a pilocytic astrocytoma of the vermis and discuss the pathophysiology of this syndrome. Transient mutism has been described for the first time quite recently, even in cases where these tumors were also surgically removed before. Perhaps improvement in imaging and in surgical techniques made neurosurgeons more daring and some interventions that were judged impossible are routinely performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…A younger age at diagnosis and radiation treatment in children with primitive neuroectoermal cerebellar tumors is associated with poorer outcome (Hoppe-Hirsch et al, 1990; Radcliffe et al, 1994). A form of acquired aphasia, mutism with subsequent dysarthria in which previously acquired language skills are lost (DiCataldo et al, 2001; Dailey et al, 1995; Doxey et al, 1999; Huber-Okrainec et al, 2001; Humphreys, 1989; Rekate et al, 1985; Van Dongen et al, 1994; Van Mourik et al, 1998) has been identified in children, but not in adults, after surgery for posterior fossa tumors. While both childhood and adult cerebellar lesions produce a “cerebellar cognitive affective syndrome” (Schmahmann, 2010), adult cerebellar damage generally results in milder and/or more transient cognitive difficulties (Alexander et al, 2012).…”
Section: The Young Age Plasticity Privilege Has Been Overstatedmentioning
confidence: 99%
“…A younger age at diagnosis and radiation treatment in children with primitive neuroectoermal cerebellar tumors is associated with poorer outcome (Hoppe-Hirsch et al, 1990; Radcliffe et al, 1994). A form of acquired aphasia, mutism with subsequent dysarthria in which previously acquired language skills are lost (DiCataldo et al, 2001; Dailey et al, 1995; Doxey et al, 1999; Huber-Okrainec et al, 2001; Humphreys, 1989; Rekate et al, 1985; Van Dongen et al, 1994; Van Mourik et al, 1998) has been identified in children, but not in adults, after surgery for posterior fossa tumors. While both childhood and adult cerebellar lesions produce a “cerebellar cognitive affective syndrome” (Schmahmann, 2010), adult cerebellar damage generally results in milder and/or more transient cognitive difficulties (Alexander et al, 2012).…”
Section: The Young Age Plasticity Privilege Has Been Overstatedmentioning
confidence: 99%
“…Some investigators believe that more aggressive surgical technique may determine who develops CMS. Di Cataldo et al [2001] pointed out that CMS had not been reported prior to 1985, and speculated that improvements in imaging and surgical techniques have made neurosurgeons more willing to attempt interventions previously judged impossible. CMS has been shown to occur more often in patients with radical resection than in patients with residual tumors [Van Calenbergh et al, 1995].…”
Section: Cause/mechanism Of Injurymentioning
confidence: 97%
“…Its cause is not well understood, though it resolves in several weeks [27]. Mutism may involve damage to the cerebellar vermis, the dentate nucleus [28], or decreased cerebral blood flow to the higher centers secondary to postoperative edema.…”
Section: Mutismmentioning
confidence: 98%